RNA Interference (RNAi) as a Potential Tool for Control of Mycotoxin Contamination in Crop Plants: Concepts and Considerations - Majumdar, Rajtilak; Rajasekaran, Kanniah; Cary, Jeffrey W. (Frontiers in Plant Science, 2017)
Mycotoxin contamination in food and feed crops is a major concern worldwide. Fungal pathogens of the genera Aspergillus, Fusarium, and Penicillium are a major threat to food and feed crops due to production of mycotoxins such as aflatoxins, 4-deoxynivalenol, patulin, and numerous other toxic secondary metabolites that substantially reduce the value of the crop. While host resistance genes are frequently used to introgress disease resistance into elite germplasm, either through traditional breeding or transgenic approaches, such resistance is often compromised by the evolving pathogen over time. RNAi-based host-induced gene silencing (HIGS) of key genes required by the pathogen for optimal growth, virulence and/or toxin production, can serve as an alternative, pre-harvest approach for disease control. RNAi represents a robust and efficient tool that can be used in a highly targeted, tissue specific manner to combat mycotoxigenic fungi infecting crop plants. Successful transgenic RNAi implementation depends on several factors including 1) designing vectors to produce double-stranded RNAs (dsRNAs) that will generate small interfering RNA (siRNA) species for optimal gene silencing and reduced potential for off-target effects; 2) availability of ample target siRNAs at the infection site; 3) efficient uptake of siRNAs by the fungus; 4) siRNA half-life and 5) amplification of the silencing effect. This review provides a critical and comprehensive evaluation of the published literature on the use of RNAi-based approaches to control mycotoxin contamination in crop plants. It also examines experimental strategies used to better understand the mode of action of RNAi with the aim of eliminating mycotoxin contamination, thereby improving food and feed safety.